Start-up marketing strategies in India - Ramesh, M. Anil; Grover, Priya; Dasgupta, Sabyasachi (Emerald Publishing Limited, 2019)
Start-up Marketing Strategies in India analyses real-life marketing challenges faced by Indian start-ups from across the marketing mix of Product, Price, Place & Promotion.Eleven original case studies discuss the experiences of successful Indian entrepreneurs across a wide variety of sectors, including Health Tech, Fintech, media and entertainment, and Fast-Moving Consumer Goods (FMCG). Each case investigates the dilemmas faced by Indian start-ups on issues in their marketing mix and presents guidance on practical ways to resolve them through fine-tuning the marketing strategy. A special focus is placed on the views and actions of the start-up founder(s) or CEO dealing with the dilemma, to highlight their innovative solutions.The book is a highly informative guide for entrepreneurs, marketing scholars and practitioners who wish to explore the marketing challenges that new companies face and find new ways to overcome them.
Includes index.
Keywords: New business enterprises -- India -- Marketing.; Business & Economics -- Marketing -- General.; Sales & marketing.; elektronické knihy; electronic books